The relationship between burn area and severity and length of stay in burn patients treated at the leading referral burn Centre in West Java, Indonesia - Patricia Andini; Arif Tri Prasetyo; Lisa Y. Hasibuan; Hardisiswo Soedjana; Filla Reviyani Suryaningrat (Burns Open)
Background: Burns are severe injuries that require intensive medical care and have a significant impact on patients’ healing and rehabilitation processes. The outcome of burn treatment is largely influenced by the length of hospital stay, which is primarily determined by the surface area and severity of the burns. This study aims to examine the relationship between the extent (≥20 % TBSA) and severity of burns with prolonged hospitalization (≥14 days) in burn patients at the Burn Unit of Dr. Hasan Sadikin General Hospital, Bandung, from January 2021 to December 2023. Methods: This research is an observational analytical correlational study using a cross-sectional approach. The subjects were burn patients hospitalized in the Burn Unit of Dr. Hasan Sadikin General Hospital during the same period, with data collected from their medical records. Out of 195 cases, only 82 were deemed suitable for evaluation. Statistical analysis of the categorical data was performed using the Chi-square test. Results: The results indicated a significant relationship between the extent of burns and the length of hospital stay in patients who showed improvement, with a p-value of 0.003 and an Odds Ratio (OR) of 6.111. A significant relationship was also found between the severity of burns and the length of stay, with a p-value of 0.025 and an OR of 3.667. However, no significant relationship was observed between the extent of burns and the length of stay in patients who did not survive. Conclusion: This study reveals a significant relationship between the extent and severity of burns and the length of hospital stay in patients who showed improvement in the Burn Unit of Dr. Hasan Sadikin General Hospital from January 2021 to December 2023.